Relationship between mental skill and anxiety interpretation in secondary school hockey athletes - Dominikus, Filino; Omar Fauzee, Mohd Sofian; Abdullah, Maria Chong; Meesin, Charoon; Choosakul, Chairat (Eurojournals, 2009)
This research was carried out to examine the relationship between mental skills and anxiety interpretation in secondary school hockey athletes. There are 108 participants (54 males, 54 females) aged between 14 and 17. These participants are athletes from three secondary schools. The average age of the participant is 15.17 (SD = 1.18). The results indicated that the direction of anxiety interpretation between the male and female athletes are the same but different in terms of intensity (coginitive anxiety interpretation direction, somatic anxiety and self confidence). Based on the predicted mental skills of athletes, it was concluded that self belief (M = 1.54 for males and M = 1.06 for females) was seen as the motivating factor or facilitative to the performance of the athletes. There was also a difference on how mental skills are related to anxiety intensity and self confidence. Recommendations for future research were also suggested.